It Takes Two to Tango: How the COVID-19 Vaccination Campaign in Israel Was Framed by the Health Ministry vs. the Television News - Gesser-Edelsburg, Anat; Hijazi, Rana; Cohen, Ricky (Frontiers in Public Health, 2022)
Background The internet has become a major resource in information transfer during COVID-19, and traditional means of communication are digitized and accessible online to the public at large. Objectives This study seeks to examine how Israel’s two main television news channels (Channel 12 and Channel 13) covered the Covid-19 vaccination campaign, compared to how the Ministry of Health ran the campaign. Methods A qualitative study based on triangulation of online content analyses from three different sources: advertising campaigns, social media posts and reports on television news channels. The research sample included 252 reports from the newsrooms of Channel 13 (n=151) and Channel N12 (n=101), Israel’s two leading news channels, all broadcast between December 1, 2020 and November 30, 2021. The sample also included posts from Israel Ministry of Health Facebook page and advertising campaigns from the Facebook page of the Israel Government Advertising Agency (LAPAM), which constructs advertising campaigns for the MOH (113 items). Results The research findings reveal congruence between the way the MOH framed its vaccination campaign and news coverage of the vaccination issue. The vaccination campaign used three primary framing strategies: 1) positive framing )emphasizing the vaccine’s advantages and stressing that the vaccine is safe and effective based on cost-benefit calculations and public health perspectives); 2) fear appeal strategy (conveying persuasive messages that seek to arouse fear through threats of impending danger or harm); 3) attribution of responsibility strategy (blaming the unvaccinated and targeting all those who criticized Israel’s generic vaccination policy). Conclusion As the watchdog of democracy, the news should function as a professional and objective source that criticizes government systems if necessary and strives to uncover the truth throughout the crisis. Public trust, which is so essential during such a crisis, can be achieved only if the news channels provide reports and meaningful journalistic investigations that challenge the system. By doing so, they can help fight conflicts of interest that divert management of the crisis from the professional health field to the political-economic arena.